Successful removal of polyacrylamide hydrogel by pulsed fiberoptic 1444-nm Nd-YAG laser. (December 2013) - Radmanesh, Mohammad; Radmanesh, Ramin; Bahadoram, Mohammad
Abstract: Background : Tissue augmentation by polyacrylamide gel (PAAG) may lead to displacement or complications several years later and necessitate its removal. Objective: To use a fiberoptic 1444-nm neodymium-doped yttrium aluminum garnet (Nd-YAG) laser for removing polyacrylamide hydrogel augmentations. Methods: Five patients with frontal and cheek augmentations were referred for gel removal. After nerve block anesthesia, a 600-μm optical fiber tip with a metallic cannula was inserted into a hole created by a 16-gauge needle, and the laser was triggered. The cannula was moved in a fan pattern in the augmented area and was then removed. The tissue was squeezed from its outermost region toward the hole to extrude the gel. The laser system used was a 1444-nm fiberoptic Nd-YAG, obtained from Lutronic lasers, South Korea. The parameters used were: pulse rate = 30, pulse energy = 150 J, power = 4.5 W, and total energy = 400–1200 J. Results: The heat of the laser tip liquefies the gel and by coagulating the surrounding tissues, it produces multiple patent canals. These two factors facilitate gel removal by squeezing the tissues. No temporary or permanent complication, such as hematoma, burning, or fibrosis, was detected. Conclusion: The 1444-nm Nd-YAG laser is a safe and efficient method for removing subcutaneous polyacrylamide hydrogel.